Can the neutrophil-to-lymphocyte ratio be used as an early marker of small fetuses for gestational age? A prospective study - Salomon, David; Fruscalzo, Arrigo; Boulvain, Michel; Feki, Anis; Ben Ali, Nordine (Frontiers in Medicine, 2024)
Background : Small-for-gestational-age (SGA) fetuses are at increased risk of mortality and morbidity, and less than 30 % will be detected by any ultrasound scan within 4 weeks before delivery. Our aim was to evaluate the relationship between neutrophil/lymphocyte ratio (NLR) in the first trimester of pregnancy and SGA fetuses. Method : We performed a prospective study between June 2021 and August 2022, to evaluate the relationship between the neutrophil to lymphocyte ratio in maternal blood in the first trimester of pregnancy, with the birth of an SGA fetus. 194 participants with singleton pregnancies between 11+1 and 13+6 weeks of gestation were recruited. Pregnancies affected with diagnosed fetal chromosomal abnormalities, or chronic pathologies were excluded. SGA was defined as birthweight less than the 10 th centile (N=42) and severe SGA as birthweight less than the 3 rd centile for gestation (N=10) according to a locally derived descriptive charts. The NLR value measured in the first trimester was compared between these two groups and controls. Results : We found no statistically significant difference in NLR, (3.5 +/-1.2 vs 3.4+/-1.2, pvalue of 0.78) when comparing the SGA less than the 10th centile group to the control group. NLR was also not different between severe SGA and controls (3.6+/-1.4 vs 3.4+/-1.2 p-value of 0.78). Conclusion : We found no association between first-trimester NLR ratio and SGA.